2015
DOI: 10.3389/fgene.2014.00450
|View full text |Cite
|
Sign up to set email alerts
|

Lupus risk variants in the PXK locus alter B-cell receptor internalization

Abstract: Genome wide association studies have identified variants in PXK that confer risk for humoral autoimmune diseases, including systemic lupus erythematosus (SLE or lupus), rheumatoid arthritis and more recently systemic sclerosis. While PXK is involved in trafficking of epidermal growth factor Receptor (EGFR) in COS-7 cells, mechanisms linking PXK to lupus pathophysiology have remained undefined. In an effort to uncover the mechanism at this locus that increases lupus-risk, we undertook a fine-mapping analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 58 publications
(72 reference statements)
0
25
0
Order By: Relevance
“…Paraxylene–Orthoxylene domain containing serine/threonine kinase is a protein that plays a role in the ligand-induced internalization, degradation, and trafficking of epidermal growth factors. Variation in PXK is association with SLE susceptibility where it is found to alter B-cell receptor internalization ( 131 ). PXK rs2176082 and rs4681851 are associated with SSc and rs2176082 has association for ACA positivity.…”
Section: Interferon-regulated Genes and Pahmentioning
confidence: 99%
“…Paraxylene–Orthoxylene domain containing serine/threonine kinase is a protein that plays a role in the ligand-induced internalization, degradation, and trafficking of epidermal growth factors. Variation in PXK is association with SLE susceptibility where it is found to alter B-cell receptor internalization ( 131 ). PXK rs2176082 and rs4681851 are associated with SSc and rs2176082 has association for ACA positivity.…”
Section: Interferon-regulated Genes and Pahmentioning
confidence: 99%
“…STAT6 is a transcription factor that is activated by the allergy-associated cytokines IL-4 and IL-13 and possibly IL-33. 5256 Esophageal epithelial cell lines have intact STAT6 signaling, 5759 and STAT6 drives the expression of many of the genes in the EoE transcriptome. 7,58,60 Indeed, STAT6 had a critical and established role in the pathophysiology of EoE before its identification as an EoE-risk locus.…”
Section: Eoe-risk Locimentioning
confidence: 99%
“…Regarding functional consequences of the PXK region SNP, one study has reported that it influenced the rate of BCR internalization, and that subjects carrying the risk haplotype had a decreased rate of BCR internalization, a process known to impact B cell survival and cell fate [ 52 ]. CTSB encodes Cathepsin B, a lysosomal cysteine protease with a poorly studied function, but which potentially may play a role in protein turnover [ 53 ].…”
Section: Discussionmentioning
confidence: 99%